Game Of Life Economics Of The Contraception Market - Řípová, Eva (2009)
This thesis deals with the contraception market in the context of decision making about children, trying to outline the consequences of this market for the economy as a whole. The first section introduces the market and defines the key role of the market for the women making the decision. The second part introduces the agents in the market with their incentives and motivations. The third part moves into closer detail paying attention mainly to choice problems and uncertainty problems. The forth part focuses on game theoretical framework and various strategies from which the players are choosing. The fifth part presents a range of models for situations in the market derived from "games" on the prisoner's dilemma principle. These games result in the hypotheses involving consequences of particular behaviour in the market. The sixth part tests the hypotheses from the previous chapter, using evidence from selected countries including Czech Republic, United Kingdom, United States, and China. The conclusion specifies future development that is uncertain but based on the current facts.